2013
DOI: 10.1136/amiajnl-2012-001555
|View full text |Cite
|
Sign up to set email alerts
|

Indication-based prescribing prevents wrong-patient medication errors in computerized provider order entry (CPOE)

Abstract: Objective To determine whether indication-based computer order entry alerts intercept wrong-patient medication errors. Materials and methods At an academic medical center serving inpatients and outpatients, we developed and implemented a clinical decision support system to prompt clinicians for indications when certain medications were ordered without an appropriately coded indication on the problem list. Among all the alerts that fired, we identified every instance when a medication order was started but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 20 publications
0
44
0
1
Order By: Relevance
“…Additional strategies aimed at preventing wrong-patient orders include using electronic decision support to verify patient identification before placing orders or alerting providers when orders are not consistent with the diseases listed in the problem list. 6,21,22 However, these interventions can be costly, dependent on the type of CPOE system, and their effectiveness may diminish over time due to alert fatigue. 23 Replacing a nondistinct naming convention with one that uses distinct names is a simple and effective intervention that is not costly, labor intensive, or dependent on new technology and may be easily implemented in most NICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional strategies aimed at preventing wrong-patient orders include using electronic decision support to verify patient identification before placing orders or alerting providers when orders are not consistent with the diseases listed in the problem list. 6,21,22 However, these interventions can be costly, dependent on the type of CPOE system, and their effectiveness may diminish over time due to alert fatigue. 23 Replacing a nondistinct naming convention with one that uses distinct names is a simple and effective intervention that is not costly, labor intensive, or dependent on new technology and may be easily implemented in most NICUs.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported a patient-note mismatch rate of 0.5% and a 40% reduction of mismatches after the implementation of patient verification module. 21 Galanter et al found that a mandatory “indication” field in the CPOE might assist the providers with avoiding wrong-patient orders for medications, and estimated that over a 6 year period, 32 wrong-patient errors were intercepted as a result of this intervention 22 . Finally, Adelman et al studied two patient verification procedures prior to entering orders: the ‘ID-verify alert’, a verification module showing the patient’s name, age and gender, and the more complex ‘ID-reentry function’, which required the provider to re-enter the initials, gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…When user is writing the prescription, this 4 Extracted structured information from Wikipedia available at dbpedia.org 5 A bioinformatics and cheminformatics resource that combines detailed drug (i.e. chemical, pharmacological and pharmaceutical) data with comprehensive drug target (i.e.…”
Section: A Architecturementioning
confidence: 99%
“…[3]. As recently published by [4] hospitals' use of computerized prescriptions prevented 17 million drug errors in a single year in the United States. The Canadian Medical Association (CMA) and the Canadian Pharmacists Association (CPhA) have approved a joint statement on the future of e-prescribing that aims to have all prescriptions for Canadians created, signed and transmitted electronically by 2015.…”
Section: Introductionmentioning
confidence: 99%